Digital Communication Strategy in Organizational Operations: Communication Transformation in The Digital Age - La Jaali (MSJ : Majority Science Journal, 2026)
Digital transformation has fundamentally reshaped communication strategies within organizational operations. This literature review examines how organizations adapt their communication frameworks to meet the demands of the digital era. The study synthesizes recent empirical and theoretical research (2023–2026) to identify key models, barriers, and strategic opportunities in digital organizational communication. Using a systematic literature review methodology, 20 peer-reviewed journals were analyzed covering dimensions of internal and external communication, leadership communication, digital tool adoption, and organizational culture. Findings reveal that effective digital communication strategies enhance employee performance, leadership quality, and organizational agility. However, organizations face challenges including information overload, resistance to change, and cultural misalignment. The study contributes a conceptual matrix framework for developing digital internal communication strategies tailored to organizational contexts. Implications for practitioners and policymakers are discussed.